Health conditions in rural areas with high livestock density: Analysis of seven consecutive years. (March 2017) - van Dijk, Christel E.; Zock, Jan-Paul; Baliatsas, Christos; Smit, Lidwien A.M.; Borlée, Floor; Spreeuwenberg, Peter; Heederik, Dick; Yzermans, C. Joris
Abstract: Previous studies investigating health conditions of individuals living near livestock farms generally assessed short time windows. We aimed to take time-specific differences into account and to compare the prevalence of various health conditions over seven consecutive years. The sample consisted of 156, 690 individuals registered in 33 general practices in a (rural) area with a high livestock density and 101, 015 patients from 23 practices in other (control) areas in the Netherlands. Prevalence of health conditions were assessed using 2007–2013 electronic health record (EHR) data. Two methods were employed to assess exposure: 1) Comparisons between the study and control areas in relation to health problems, 2) Use of individual estimates of livestock exposure (in the study area) based on Geographic Information System (GIS) data. A higher prevalence of chronic bronchitis/bronchiectasis, lower respiratory tract infections and vertiginous syndrome and lower prevalence of respiratory symptoms and emphysema/COPD was found in the study area compared with the control area. A shorter distance to the nearest farm was associated with a lower prevalence of upper respiratory tract infections, respiratory symptoms, asthma, COPD/emphysema, allergic rhinitis, depression, eczema, vertiginous syndrome, dizziness and gastrointestinal infections. Especially exposure to cattle was associated with less health conditions. Living within 500m of mink farms was associated with increased chronic enteritis/ulcerative colitis. Livestock-related exposures did not seem to be an environmental risk factor for the occurrence of health conditions. Nevertheless, lower respiratory tract infections, chronic bronchitis and vertiginous syndrome were more common in the area with a high livestock density. The association between exposure to minks and chronic enteritis/ulcerative colitis remains to be elucidated. Graphical abstract: Highlights: Livestock exposure was not a risk factor for the occurrence of health conditions. Respiratory problems and vertiginous syndrome were more common in the study area. Future research should also investigate possible health effects from mink exposure. Abstract : In general, livestock exposure was not a risk factor for the occurrence of health conditions. However, compared to the control areas, respiratory problems and vertiginous syndrome were more common in the study areas.